2014
DOI: 10.1371/journal.pone.0113583
|View full text |Cite|
|
Sign up to set email alerts
|

Development of β-Carotene Rich Maize Hybrids through Marker-Assisted Introgression of β-carotene hydroxylase Allele

Abstract: Development of vitamin A-rich cereals can help in alleviating the widespread problem of vitamin A deficiency. We report here significant enhancement of kernel β-carotene in elite maize genotypes through accelerated marker-assisted backcross breeding. A favourable allele (543 bp) of the β-carotene hydroxylase (crtRB1) gene was introgressed in the seven elite inbred parents, which were low (1.4 µg/g) in kernel β-carotene, by using a crtRB1-specific DNA marker for foreground selection. About 90% of the recurrent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
154
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(174 citation statements)
references
References 38 publications
15
154
5
Order By: Relevance
“…The crtRB1 gene has been reported to be a major gene affecting two-to tenfold accumulation of β-carotene in maize kernel (Babu et al 2013;Choudhary et al 2014;Muthusamy et al 2014). Though both the lines and testers possessed the favourable allele for crtRB1 3'TE gene which is known to cause higher accumulation of β-carotene, quite contrasting β-carotene concentration was observed between them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The crtRB1 gene has been reported to be a major gene affecting two-to tenfold accumulation of β-carotene in maize kernel (Babu et al 2013;Choudhary et al 2014;Muthusamy et al 2014). Though both the lines and testers possessed the favourable allele for crtRB1 3'TE gene which is known to cause higher accumulation of β-carotene, quite contrasting β-carotene concentration was observed between them.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we hypothesize here that allele from CIMMYT-HarvestPlus origin should be in homozygous condition to reap the benefit of the allele effect. Considering this, markeraided introgression of this allele would be an effective strategy for provitamin A enrichment programme (Babu et al 2013;Muthusamy et al 2014).…”
Section: Cereal Research Communications 44 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…In the similar line of work, marker-assisted backcross breeding (MABB) has been also used to develop maize genotypes for reduced anti-nutritional factors (Naidoo et al 2012). Muthusamy et al (2014) developed ß-Carotene rich maize hybrids through marker-assisted introgression of ß-carotene hydroxylase allele. Chander et al (2008) identified a major locus (y1) for carotenoid content using gene targeted molecular marker (Y1ssr).…”
Section: Breeding For Quality Protein Maize (Qpm)mentioning
confidence: 99%
“…While β-carotene is low in maize kernels [52], maize displays a genetic variation in carotenoid contents [53]. In yellow kernels, β-carotene ranges from 0.01 to 4.7 mg g -1 [54] although most yellow varieties consumed contain only 0.5 to 1.5 mg g -1 [53]. Additionally, utilization of yellow maize for livestock feed hinders human consumption in parts of Southern Africa where white maize, lacking pVA, is preferred [55].…”
Section: Development Of Transgenic Pro-vitamin a Enhanced Maizementioning
confidence: 99%